2009
DOI: 10.12795/ambitos.2009.i18.06
|View full text |Cite
|
Sign up to set email alerts
|

La influencia de la sitcom americana en la producción de comedias televisivas en España. El caso de "Friends" y "7 vidas".

Abstract: Este artículo tiene como objetivo principal explicar la influencia de la sitcom norteamericana en la producción de comedias televisivas españolas con el fin de obtener los estándares de producción de este formato en España. Se tratará, en concreto, el caso de "Friends" y "7 vidas" por ser el más paradigmático de este fenómeno. La estandarización y profesionalización del proceso creativo así como el alargamiento de la duración serán algunos aspectos característicos tratados en la producción de sitcoms en España. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Different articles were identified that covered certain periods, such as a series produced during Franco's regime, created by Jaime de Armiñán (Diego and Grandío, 2014); a series that were restricted to the family environment (Hidalgo-Marí, 2018); and those that studied the entire 1990-2018 period (Gómez, 2020;Gómez, 2017;Diego and Grandío, 2011). Yet another alluded to more experimental Spanish sitcoms, in tune with and influenced by new international formats, such as Siete Vidas and Qué fue de Jorge Sanz (Fernández and Aguado, 2013;Grandío and Diego, 2009). Another genre discussed in the papers reviewed was police drama (4).…”
Section: Figure 4 Number Of Articles Published By Type Of Studymentioning
confidence: 99%
“…Different articles were identified that covered certain periods, such as a series produced during Franco's regime, created by Jaime de Armiñán (Diego and Grandío, 2014); a series that were restricted to the family environment (Hidalgo-Marí, 2018); and those that studied the entire 1990-2018 period (Gómez, 2020;Gómez, 2017;Diego and Grandío, 2011). Yet another alluded to more experimental Spanish sitcoms, in tune with and influenced by new international formats, such as Siete Vidas and Qué fue de Jorge Sanz (Fernández and Aguado, 2013;Grandío and Diego, 2009). Another genre discussed in the papers reviewed was police drama (4).…”
Section: Figure 4 Number Of Articles Published By Type Of Studymentioning
confidence: 99%
“…La comedia en televisión ha sido uno de los géneros más exitosos y también más variados de la historia de la televisión (Bounaut y Grandío, 2009). Su permanencia se ha debido a su capacidad de adecuarse a las nuevas tendencias aparecidas en el medio televisivo a lo largo de los años y reinventarse continuamente para seguir conquistando a la audiencia.…”
Section: Marco Teóricounclassified
“…In Spain, some outstanding studies include the analysis of gender stereotypes in two Spanish series by Galán-Fajardo (2007), the study by Belmonte and Guillamón (2008) about gender stereotypes in the series most frequently viewed by Spanish youth, the study by Ramajo et al (2008) on teen representations on primetime television in Spain, the study by Guarinos (2009) about prototypical representations of teens in fiction products broadcast in Spain and targeted at a young audience, and the sitcom study carried out by Grandío-Pérez and Pedro-González (2009).…”
Section: Literature Reviewmentioning
confidence: 99%